2019
DOI: 10.1016/j.ekir.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Sotatercept Safety and Effects on Hemoglobin, Bone, and Vascular Calcification

Abstract: IntroductionPatients with end-stage kidney disease (ESKD) exhibit anemia, chronic kidney disease‒mineral bone disorder (CKD–MBD), and cardiovascular disease. The REN-001 and REN-002 phase II, multicenter, randomized studies examined safety, tolerability, and effects of sotatercept, an ActRIIA-IgG1 fusion protein trap, on hemoglobin concentration; REN-001 also explored effects on bone mineral density (BMD) and abdominal aortic vascular calcification.MethodsForty-three patients were treated in REN-001 (dose rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…It was also associated with clinically meaningful improvements in 6-min walk distance and circulating levels of N-terminal pro-B-type natriuretic peptide, a marker for cardiac dysfunction. Sotatercept has previously been evaluated in healthy volunteers and patients with conditions characterized by dysfunctional TGF-β superfamily signaling, including anemia associated with myelodysplastic syndromes, anemia associated with β-thalassemia, chemotherapy-induced anemia, end-stage kidney disease, bone loss, and multiple myeloma ( 168 174 ). As a result, substantial data are already available regarding sotatercept's safety profile.…”
Section: Targeting Overactive Smad2/3 Pathway Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also associated with clinically meaningful improvements in 6-min walk distance and circulating levels of N-terminal pro-B-type natriuretic peptide, a marker for cardiac dysfunction. Sotatercept has previously been evaluated in healthy volunteers and patients with conditions characterized by dysfunctional TGF-β superfamily signaling, including anemia associated with myelodysplastic syndromes, anemia associated with β-thalassemia, chemotherapy-induced anemia, end-stage kidney disease, bone loss, and multiple myeloma ( 168 174 ). As a result, substantial data are already available regarding sotatercept's safety profile.…”
Section: Targeting Overactive Smad2/3 Pathway Signalingmentioning
confidence: 99%
“…Ongoing clinical studies of sotatercept in PAH patients include a phase 2 study for detailed characterization of cardiopulmonary status by right heart catheterization with exercise (NCT03738150) and several phase 3 registration-enabling studies (NCT04576988, NCT04811092, NCT04896008). Interestingly, several clinical studies have determined that sotatercept increases circulating hemoglobin concentrations under diverse conditions ( 169 , 171 174 ). It has been observed that a large proportion of PAH patients exhibits anemia and could therefore receive sotatercept with acceptable erythropoietic effects ( 175 ).…”
Section: Targeting Overactive Smad2/3 Pathway Signalingmentioning
confidence: 99%
“…Finally, the fact that a statin paradox exists (statins promoted coronary atheroma calcification but improved clinical outcomes) (149) means that the implication of VC may be reconsidered (150). Nevertheless, many experimental and/or preliminary clinical studies on VC with different compounds are ongoing (151)(152)(153)(154)(155)(156)(157)(158)(159)(160). Thus, other factors (directly or indirectly related with CKD-MBD) such as magnesium, vitamin K, inhibitors of intestinal P transporters, bisphosphonates, denosumab, sodium thiosulfate, alkaline phosphatase inhibitors, apabetalone, sotatercept, recombinant BMP-7, as well as metformin, antioxidants, spironolactone, senolytics, zinc, and the recently tested SNF472 (35, 161, 162) have been shown to potentially attenuate VC.…”
Section: Treatment For Hyperparathyroidismmentioning
confidence: 99%
“…Interestingly, sotatercept was also tested in HD patients in two phase II, multicenter, randomized trials, REN-001 and REN-002 [124]. In these studies, the safety, tolerability, and effects of different dosages of sotatercept (from 0.1 to 0.7 mg/kg) on hemoglobin concentration were evaluated; in addition, in REN-001, the effects of sotatercept on bone mineral density (BMD) and abdominal aortic vascular calcification were also explored.…”
Section: Clinical Therapeutic Developmentsmentioning
confidence: 99%